Growth and Performance Analysis of Corporate Sukuk in Indonesia: A Case Study of the 2019-2024 Period: Analisis Pertumbuhan dan Performa Sukuk Korporasi di Indonesia: Studi Kasus Periode 2019-2024 - Ahyak (Program Studi Ekonomi Syariah & LP2M STAI Az-Zain Sampang, 2024)
The increasing interest in corporate sukuk in Indonesia shows great potential as an Islamic financial instrument, but in-depth research on the factors that influence its growth is still limited. This study aims to analyze the growth and performance of corporate sukuk in Indonesia during the 2019-2024 period, as well as identify the factors that influence it. This research method uses a descriptive-analytical quantitative approach with trend analysis and linear regression on secondary data from OJK reports, Bank Indonesia, and national statistical agencies. The results showed a significant increase in total sukuk issuance from IDR 25 trillion in 2019 to IDR 40 trillion in 2024, with a low default rate of below 1%. Factors such as government policies, macroeconomic conditions, and increased public awareness of Islamic finance play an important role in this growth. The implications of this study emphasize the importance of policy support and public education to encourage more sustainable development of the corporate sukuk market in Indonesia